DNA barcoding and biomass accumulation rates of native Iranian duckweed species for biotechnological applications - Taghipour, Elham; Bog, Manuela; Frootan, Fateme; Shojaei, Sadegh; Rad, Nima; Arezoumandi, Mahdi; Jafari, Mahyat; Salmanian, Ali Hatef (Frontiers in Plant Science, 2022)
The Lemnaceae family (duckweed) consists of at least three recognized genera with six reported species in Iran which are distributed in wetlands. Duckweeds are the simplest and smallest flowering aquatic monocots with free floating fronds that can reproduce asexually every 2-3 days. Duckweed could be a major source of balanced amino acids and high protein content, which is increasingly promising for biotechnological applications. For molecular classification and species identification of the collected samples, DNA barcoding was performed using two standard chloroplast markers, the spacer region between the ATP synthase subunits F and H (atpF-atpH) and the intron region of the ribosomal protein S16 (rps16). The results confirmed the presence of four species belonging to the two genera Lemna and Spirodela. In addition, L. turionifera was detected for the first time in Iran. Due to the high growth rates of duckweed, measurement of biomass accumulation and doubling time are important factors in determining the growth potential, especially for native species. The relative growth rates (RGR), doubling times (DT), biomass accumulation (BA) and relative weekly yields (RY) of 40 distinct duckweed clones were determined under standard cultivation conditions. The dry weight based RGR ranged from 0.149 to more than 0.600 per day, DT from 1.12 to 9 days and RY from 7 to 108.9 per week. All values are comparable with previous studies. RGR and RY of selected clones are higher than the growth potential for a wide range of wild plants and common crops. These data support that native duckweed has high productivity value and should be further investigated as a potentially rich protein source for alternative human food, livestock feed, and recombinant protein production.